STUDENTS’ PERCEPTION OF USING G-SUITE IN LEARNING SPEAKING AT SMA NEGERI 3 PALU - Sri Masriyani; Nadrun Nadrun; Afrillia Anggreni (Tadulako University, 2022)
The objective of this research is to find out the students’ perception on the use of G-Suite application in learning speaking during the Covid-19 Pandemic era. Qualitative descriptive research was used by involving 36 students of the tenth-grade IPA 8 who have experienced in learning speaking by using the G-Suite application at SMA Negeri 3 Palu. Questionnaire and interview were employed to collect the data. The questionnaires in this research consist of 2 indicators, namely the effectiveness of G-Suite and the effect to speaking component. The interview was conduct to get more information from the students as a supporting result of the questionnaire. Based on the analysis of data, the conclusion can be drawn that students’ perception of using G-Suite in learning speaking during the Covid-19 Pandemic effective and have a positive perception. It can be seen from the percentage of the data based on the questionnaire related to the effectiveness of G-Suite and the effect to speaking component. Perception related to the effectiveness of G-Suite showed the highest frequency with a percentage 94.4%, and perception related the effect to speaking component showed the highest frequency with a percentage 88.9%. From the finding, using G-Suite in learning speaking quite help for students and teacher during the Covid-19 Pandemic.